2022
DOI: 10.1038/s41467-022-32015-7
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of Blautia wexlerae ameliorates obesity and type 2 diabetes via metabolic remodeling of the gut microbiota

Abstract: The gut microbiome is an important determinant in various diseases. Here we perform a cross-sectional study of Japanese adults and identify the Blautia genus, especially B. wexlerae, as a commensal bacterium that is inversely correlated with obesity and type 2 diabetes mellitus. Oral administration of B. wexlerae to mice induce metabolic changes and anti-inflammatory effects that decrease both high-fat diet–induced obesity and diabetes. The beneficial effects of B. wexlerae are correlated with unique amino-aci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(117 citation statements)
references
References 107 publications
(133 reference statements)
6
91
0
Order By: Relevance
“…Compared with the NC diet, LPF treatment significantly enriched SCFA-producing bacteria such as Megasphaera, Roseburia, Faecalibacterium, Blautia, Selenomonas, Dialister, Acidaminococcus, Ruminococcus, and Bifidobacterium (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Some of those bacteria also have other beneficial functions, for example, Megasphaera could enhance large intestine functions and effectively prevent hyper-lactate accumulation-related diarrhea (42), Roseburia has benefits from immune modulation to inflammatory regulation (43), Blautia and Faecalibacterium had anti-inflammatory functions to help support gut health (44)(45)(46). In addition, this study indicated that the LPF diet selectively decreased the relative abundance of Bacteroides, an acetate producer (47).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the NC diet, LPF treatment significantly enriched SCFA-producing bacteria such as Megasphaera, Roseburia, Faecalibacterium, Blautia, Selenomonas, Dialister, Acidaminococcus, Ruminococcus, and Bifidobacterium (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Some of those bacteria also have other beneficial functions, for example, Megasphaera could enhance large intestine functions and effectively prevent hyper-lactate accumulation-related diarrhea (42), Roseburia has benefits from immune modulation to inflammatory regulation (43), Blautia and Faecalibacterium had anti-inflammatory functions to help support gut health (44)(45)(46). In addition, this study indicated that the LPF diet selectively decreased the relative abundance of Bacteroides, an acetate producer (47).…”
Section: Discussionmentioning
confidence: 99%
“…Many species under the genus Lactobacillus have significant effects on glucose metabolism, and several studies have shown that treatment with Lactobacillus significantly controls elevated blood glucose and is able to regulate glucose tolerance, hepatic glycogen, and lipid metabolism (Yun et al, 2009;Dang et al, 2018;Zhou et al, 2021). Blautia is widely believed to be associated with obesity and inflammation, and it has been demonstrated that Blautia reduces obesity and diabetes caused by high-fat diet and relies on its own metabolites, such as acetic acid and SCFA, to alter the intestinal environment and block colonization by specific bacteria (Hosomi et al, 2022). Both Allobaculum and Candidatus Saccharimonas are known producers of short chain fatty acids (SCFAs), and their elevated abundance affects intestinal pH.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted in accordance with the Declaration of Helsinki and approved by the Ethnic Committee of NIBIOHN (approved number: 154−10, 177−09, 272−01) and by the Ethics Committee of the Nippn Corporation (approved number: 20−01) and adhered to all guidelines. Fecal samples were collected, mixed with 3 mL of guanidine thiocyanate solution (Techno Suruga Laboratory, Shizuoka, Japan), and stored at 4 °C [31,32]. Blood was collected, and prepared serum samples were stored at −80 °C until use.…”
Section: Subject and Sample Collectionmentioning
confidence: 99%
“…DNA extraction and 16S rRNA gene amplicon sequencing were performed as previously described [31,32]. Fecal samples mixed with guanidine thiocyanate solution were disrupted by the bead beating method using 0.1 mm glass beads.…”
Section: Gut Microbiome Analysismentioning
confidence: 99%